PEMBENTUKAN NILAI KARAKTER INTEGRITAS MELALUI GERAKAN LITERASI SEKOLAH PADA ANAK MI/SD - Vita Fitriatul Ulya; Zulfatun Anisah (PREMIERE : Journal of Islamic Elementary Education, 2021)
ABSTRACT The character of integrity is one of the main character values ​​in the Movement for Strengthening Character Education launched by the Ministry of Education and Culture in 2016. The character values ​​in question include religious, nationalist, mutual cooperation, independence and integrity. These character values ​​need to be instilled from childhood. Likewise, the character of integrity can be formed through formal education in elementary schools, one of which is through literacy programs. Elementary school level children have the characteristics of high curiosity and understand concrete things better than abstract. So that the literacy program that is applied must be interesting and fun. The literacy program has developed dynamically, which was initially only defined as the ability to read and write, then developed with the ability to think critically and speak spoken language. One form of literacy in schools is through the School Literacy Movement. One form of literacy at school is through the habit of reading books other than textbooks for 15 minutes before the lesson begins. Books that contain exemplary stories can shape children's morals. In addition, the provision of training from the teacher can train children's honesty. Giving assignments also trains children's responsibilities. It is hoped that through the literacy program, children's integrity character is formed, including honesty, love for the truth, loyalty, moral commitment, anti-corruption, justice, responsibility, example, respecting individual differences. Keywords: Formation, integrity character values, and school literacy movement